Integral Approach in Discourse Studies (Voice Messaging Study) - A. V. Kaminskaya (Дискурс, 2023)
Introduction. The article considers the issue of integral approach towards the study of a new form of discourse – voice message (VM), which possesses its social and communicative features. The topic is of particular interest to linguists and humanity studies’ scientists, since an efficient interdisciplinary approach in research is an actual issue. The nature of voice messaging is at the intersection of the interests of sociology, cognitive science, axiology and linguistics, so the use of the integral approach allows us to fully study this discursive phenomenon. The scientific novelty of the work lies in the fact that the integral approach in discourse studies has been poorly studied, and in the absence of deep studies of the voice messaging.Methodology and sources. To study the voice messaging in line with integral approach, a linguistic modeling method is used to create the integral model based on K. Wilber’s idea of AQAL (all quadrants all levels). Discursive analysis and the sociological survey method are used to describe the nature of the voice message. Using the categorical method of “formal- logical definition of the concept”, a definition of a voice message is given.Results and discussion. The use of the integral approach made it possible to create an integral model of voice communication, consisting of 4 sectors: social, cognitive, cultural and linguistic. Each sector presents a series of qualitative findings that help determine the place and role of this communicative phenomenon in the modern paradigm.Conclusion. The social sector presents the VM as a popular form of communication among people of different ages, genders and occupations, compensating for the shortcomings of modern live communication due to the dynamism of life. From the point of view of cultural studies, the communication of the VM suggests that the modern Russian person treats time as an exhaustible valuable resource; Russian-speaking culture becomes individualistic and focuses on the speaker; society values spirituality and the ability to reflect. The daily communication via VM consists of the genre repertoire, which has a high degree of emotionality: explanation, story, heart-to-heart conversation, expression of empathy, request, apology and gratitude. The cognitive sector has given knowledge about the most common emotions in the VM – joy, sadness and surprise.